2023
DOI: 10.17219/acem/159090
|View full text |Cite
|
Sign up to set email alerts
|

The time-dependent adverse effects of a high-fat diet on sperm parameters

Abstract: Background. Studies indicate a relationship between a high-fat diet (HFD) and sperm quality. However, the time-dependent adverse effects of a HFD on sperm parameters and the underlying mechanisms remain unclear.Objectives. The present study was designed to determine the effects of a HFD on sperm quality at various time points in order to assess whether a HFD causes cumulative damage to sperm. Materials and methods.Male C57BL/6 mice were fed a normal diet (the ND group) or a HFD (the HFD group) for 16, 30 or 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…Over the past few decades, a decline in semen quality parameters has been reported [28,29]. Increasing evidence suggests that lifestyle-related factors, such as tobacco, alcohol, and recreational drug consumption, obesity, advanced paternal age, physical activity, and dietary habits, play a significant role in this decline by inducing testicular damage, impaired semen parameters, and sperm DNA fragmentation [7,[9][10][11][12]30]. In the current study, we investigated the impact of several lifestyle factors, such as tobacco and alcohol consumption, the practice of physical activity, and dietary habits, on semen quality parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few decades, a decline in semen quality parameters has been reported [28,29]. Increasing evidence suggests that lifestyle-related factors, such as tobacco, alcohol, and recreational drug consumption, obesity, advanced paternal age, physical activity, and dietary habits, play a significant role in this decline by inducing testicular damage, impaired semen parameters, and sperm DNA fragmentation [7,[9][10][11][12]30]. In the current study, we investigated the impact of several lifestyle factors, such as tobacco and alcohol consumption, the practice of physical activity, and dietary habits, on semen quality parameters.…”
Section: Discussionmentioning
confidence: 99%
“…While the exact reasons for idiopathic male infertility are not fully understood, it is believed that various risk factors, including age, psychological stress and quality of life, an inadequate lifestyle, and environmental or occupational exposure to toxicants, may play a role [3][4][5][6][7][8]. Numerous studies have reported that several lifestyle factors, including tobacco smoking [9,10], alcohol consumption [9], and high-fat diets [11], can induce testicular damage, impaired semen parameters, and sperm DNA fragmentation by inducing oxidative stress and inflammation [7,12]. Regarding tobacco smoking, several animal studies have been conducted to understand the effects of cigarette consumption on testes, sperm, and semen parameters.…”
Section: Introductionmentioning
confidence: 99%